Potential of California Variety Papaya Leaf Extract (Carica papaya L. California variety) As Bioherbicide of Snake Grass Weed (Cyperus rotundus L.) - Setiawan, Riki; Mu'jijah, Mu'jijah; Suyamto, Suyamto (Biology, Medicine, & Natural Product Chemistry, 2024)
Efforts to increase production yields are by controlling weeds. Weeds that often grow and we encounter in cultivated plants are weed grass (C. rotundus). California papaya leaves have the potential to be a bioherbicide because they contain allelochemicals that can inhibit weed growth.  This study aims to determine the effect of papaya leaves (C. papaya) on the growth of teki grass (C. rotundus) and determinetheconcentration level of papaya leaf allelopathy that most effectively inhibits the growth of teki grass.The method used was a completely randomized design (CRD) with five replications and four treatmentsof0%, 30%, 50%, and 70%. For data analysis in this study using the SPSS version 25.0 program. Papaya leaf extract (C. papaya) is able to inhibit the growth of weed grass (C. rotundus). The concentration of papaya leaf extract (C. papaya) that most effectively inhibits the growth of weed is 50% concentration with a mortality rate (64%), for the lowest plant heightis50% concentration which is 13.84 cm, for the slowestgrowthrate is 50% concentrationwith a growthrate of -0.16 cm.